Perceptions of Corruption and the Dynamics of Women's Representation. Issue 3 (8th August 2014) - Watson, David; Moreland, Amy
Abstract : A growing body of literature focuses on the attitudes produced by women's representation. One area of particular interest is the effect of women's representation on perceptions of corruption in government. Multiple scholars have found that citizens view women in government as more trustworthy and less corrupt. Others have suggested that the link between gender and corruption is spurious or dependent upon regime characteristics. Additionally, many studies of women's effect on corruption were published prior to the widespread adoption of gender quotas, when levels of women's representation were considerably lower. We argue that the relationship between women and perceptions of corruption can be better understood by applying an integrated model of representation, which explores the effects of formal, descriptive, and substantive representation on perceptions of corruption. Using a time-series analysis of 140 countries worldwide from 1998–2011, this study finds that women's descriptive and substantive representation are correlated with lower perceptions of corruption. However, gender quotas are correlated with higher perceptions of corruption among political elites.